First‐in‐human safety, tolerability, and pharmacokinetic results of DFV890, an oral low‐molecular‐weight NLRP3 inhibitor - Ewa Gatlik; Beata Mehes; Emilie Voltz; Ulrike Sommer; Elaine Tritto; Giulia Lestini; Xiaoxi Liu; Parasar Pal; Maria Velinova; Wiliam S. Denney; Yunlin Fu; Anthony Opipari; et al. (Wiley, 2024)
Abstract This first‐in‐human study evaluated the safety, tolerability, single‐ and multiple‐dose pharmacokinetic profiles with dietary influence, and pharmacodynamics (PD) of DFV890, an oral NLRP3 inhibitor, in healthy participants. In total, 122 participants were enrolled into a three‐part trial including single and 2‐week multiple ascending oral doses (SAD and MAD, respectively) of DFV890, and were randomized (3:1) to DFV890 or placebo (SAD [3-600 mg] and MAD [fasted: 10-200 mg, once‐daily or fed: 25 and 50 mg, twice‐daily]). DFV890 was generally well‐tolerated. Neither deaths nor serious adverse events were reported. A less than dose‐proportional increase in exposure was observed with the initially used crystalline suspension (3-300 mg); however, an adjusted suspension formulation using spray‐dried dispersion (SDD; 100-600 mg) confirmed dose‐proportional increase in exposure. Relative bioavailability between crystalline suspension and tablets, and food effect were evaluated at 100 mg. Under fasting conditions, Cmax of the tablet yielded 78% compared with the crystalline suspension, and both formulations showed comparable AUC. The fed condition led to a 2.05‐ and 1.49‐fold increase in Cmax and AUC0-last compared with the fasting condition. The median IC50 and IC90 for ex‐vivo lipopolysaccharide‐stimulated interleukin IL‐1β release inhibition (PD) were 61 (90% CI: 50, 70) and 1340 ng/mL (90% CI: 1190, 1490). Crystalline tablets of 100 mg once‐daily or 25 mg twice‐daily were sufficient to maintain ~90% of the IL‐1β release inhibition over 24 h at steady state. Data support dose and formulation selection for further development in diseases, in which an overactivated NLRP3 represents the underlying pathophysiology.